Electronic structure and optical properties of HgSe - Akinlami, J.O.; Odeyemi, O.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
We have performed the density functional theory calculations of mercury selenide compound using the plane-wave pseudo-potential (PWPP) method within the generalized gradient approximation to investigate the electronic structure and dielectric response of this compound in its zinc blende phase. The calculated lattice and volume parameters are in consonance with other experimental and theoretical works. The electronic structure of the compound showed that mercury selenide exhibited a semi-metallic property with a negligible direct band gap of about 0 eV at the high symmetry gamma-point. Real and imaginary parts of the dielectric function as a function of photon energy have also been obtained.